Chapters of the heart : Jewish women sharing the Torah of our lives - Elwell, Ellen Sue Levi; Fuchs, Nancy (Eugene, Oregon : Cascade Books, 2013)
"Chapters of the Heart invites readers into the lives of twenty women for whom Jewish language and texts provide a lens for understanding their experiences. The authors don't just use religious words (texts, theologies, or liturgies) like a cookbook. Instead they serve readers something closer to a real meal, prepared with love and intention. Each essay shares one piece of its writer's heart, one chapter of experience as refracted through the author's particular Jewish optic. The authors write about being daughters, mothers, sisters, partners, lovers, and friends. They share their experiences of parenting, infertility, and abortion. One describes accompanying her young husband through his life-threatening illness. Another tells of her daughter's struggle with an eating disorder. Still another reflects on long decline of a parent with Alzheimer's. All these writers wrestle with Jewish texts while growing as rabbis, as feminists, and as interfaith leaders. They open their hearts and minds, telling when Jewish tradition has helped make meaning and, on occasion, when it has come up empty. The results are sometimes inspiring, sometimes provocative."--Publisher's web site.
All the days of our lives (Psalm 27:4). A life with things / Vanessa L. Ochs ; On raising a son : one mother's search for wisdom / Hara E. Person ; Between sisters / Ellen M. Umansky ; The face under the huppah : relating to my closest stranger / Nancy Fuchs Kreimer ; Loving our mothers / Vivian Mayer ; Portals to sacred family life / Julie Greenberg -- From the narrow places (Psalm 118:5). "Sing, o barren one" : ambushed by a hysterectomy at age twenty-six / Ellen Frankel ; El na refa na la : please, God, heal my daughter! / Amy Eilberg ; Facing pain, facing my fears / Ruth H. Sohn ; My mother as a ruined city : insights fro the Book of Lamentations / Rachel Adler ; Wrestling with God and evil / Judith Plaskow -- Opening the gates (Psalm 118:19). In the right time : reflections on an abortion / Sue Levi Elwell ; My life as a talking horse : hybridity and gender equaity as Jewish values / Wendy Zierler ; My interfaith friendships : blessings and challenges / Blu Greenberg ; The remembrance of these things : war, occupation, parsley, bitter herb / Margaret Holub -- Be still and know (Psalm 46:10). Shattering and rebirth : my midlife gap year / Dayle A. Friedman ; Letting go and drawing close / Laura Geller ; Leaving Egypt again : aging with awareness / Sheila Peltz Weinberg ; A heart so broken it melts like water / Barbara Eve Breitman ; With the song of songs in our hearts / Tamara Cohn Eskenazi.
Includes bibliographical references (pages 193-199).
Description based on print version record.
Keywords: Jewish women -- Religious life -- Anecdotes; Women in Judaism; Jewish women -- Religious life; Women in Judaism; RELIGION / Judaism / General; Anecdotes; Electronic books